1987
DOI: 10.1086/131989
|View full text |Cite
|
Sign up to set email alerts
|

Classification of active galaxies and the prospect of a unified phenomenology

Abstract: The observational classification of active galaxies is reviewed and its likely meaning discussed. A large number of facts and ideas are examined, but a particular set of ideas is stressed as our best hope for a unified phenomenology, as follows. There is only one kind of Active Galactic Nucleus (AGN). The observed variety arises from three degrees of freedom: (1) Dust opacity, which produces the distinction between Type 1 and Type 2 AGN. (2) Viewing angle of a relativistic jet, which produces the distinction b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
0
5

Year Published

1995
1995
2011
2011

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(54 citation statements)
references
References 91 publications
1
48
0
5
Order By: Relevance
“…Several investigations in the literature have yielded results consistent with the predictions of this scheme, e.g., the featureless continuum is stronger in Seyfert 1 than in Seyfert 2 galaxies (Lawrence 1987;Mas-Hesse et al 1994). Kinney et al (1991) showed similar ultraviolet slopes for Seyfert 2 and Seyfert 1 galaxies.…”
Section: Introductionsupporting
confidence: 71%
“…Several investigations in the literature have yielded results consistent with the predictions of this scheme, e.g., the featureless continuum is stronger in Seyfert 1 than in Seyfert 2 galaxies (Lawrence 1987;Mas-Hesse et al 1994). Kinney et al (1991) showed similar ultraviolet slopes for Seyfert 2 and Seyfert 1 galaxies.…”
Section: Introductionsupporting
confidence: 71%
“…Our understanding of AGNs is based largely on an empirical foundation that suggests a differentiation based on luminosity (Lawrence 1987). We attempt to test for this differentiation by plotting the rest-frame core RM versus 15 GHz radio luminosity in Figure 36.…”
Section: Rm and Radio Luminositymentioning
confidence: 99%
“…As in biology, however, taxonomy derived from empirical observations can impose some order on the chaos. Table 1 shows the principal classes of AGN (adapted from Lawrence 1987Lawrence , 1993, organized according to their radio loudness and their optical spectra, i.e., whether they have broad emission lines (Type 1), only narrow lines (Type 2), or weak or unusual line emission. Within each of the groupings, different types of AGN are listed by increasing luminosity.…”
Section: Observed Properties and Empirical Classification Of Agnmentioning
confidence: 99%